Reuse of cultural data - Ferrer-Sapena, Antonia; Peset, Fernanda (Anuario ThinkEPI, 2012)
The reuse of data by public administration in Spain is growing significantly thanks to Plan Avanza 2. But the growth rate is not the same in the case of cultural institutions. The three key issues that delay the release of cultural data are described: the need for adequate metrics for measuring the business generated when data become open, the possibility of losing the attribution, and potential income loss. The most emblematic cultural data release projects are described, and the problems they have faced are identified.